Dynamic Response Analysis of Super Shallow-Buried Rectangular Tunnel - Sanqing Su; Tao Yin; Zhen Cao; Bin Lei; Zhao Liu; Wenxu Lin; Anyuan Kuang (Advances in Civil Engineering)
Relying on the project of the open-cut municipal tunnel undercrossing Ankang Freight V yard, the train dynamic response and seismic response of ultrashallow-buried rectangular tunnel of the lower interchange are studied, respectively, by combining the method of field measurement and numerical simulation. The results show that under the action of train vibration load, the dynamic stress response of the top plate midspan and the upper end of the side wall of the tunnel cross section directly below the rail is the most significant, and the dynamic stress response of the bottom plate is the smallest. Under the rare earthquake, the tunnel structure has large transverse deformation, in which the transverse displacement of the tunnel roof is the largest. At the same time, there is a large stress concentration at the variable section of the tunnel.